2013
DOI: 10.4049/jimmunol.1203363
|View full text |Cite
|
Sign up to set email alerts
|

PTPN22 Modulates Macrophage Polarization and Susceptibility to Dextran Sulfate Sodium–Induced Colitis

Abstract: PTPN22, a protein tyrosine phosphatase expressed mainly in hematopoietic cells, has been linked to many autoimmune diseases. A C-to-T single nucleotide polymorphism (SNP) at position 1858 of human PTPN22 cDNA decreases the risk of Crohn’s disease. However, the function of PTPN22 and the mechanism by which this SNP reduces the risk of Crohn’s disease are poorly understood. We find that PTPN22 is expressed in macrophages. It suppresses M1 macrophage polarization and reciprocally promotes the expression of M2-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
84
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 39 publications
5
84
0
Order By: Relevance
“…However, the impaired expression of ATM and PFKFB3, which are also induced by anti-CD3 stimulation, in ARI PBMCs cannot be explained by stronger activation signals and suggests a novel mechanism. The phosphatase activity of PTPN22 also inhibits the signals induced by type I interferon (49), modulates macrophage polarization (50), and activates the inflammasome by dephosphorylating NLRP3 (51). A role of NLRP3 in Th cells was recently discovered (52).…”
Section: Discussionmentioning
confidence: 99%
“…However, the impaired expression of ATM and PFKFB3, which are also induced by anti-CD3 stimulation, in ARI PBMCs cannot be explained by stronger activation signals and suggests a novel mechanism. The phosphatase activity of PTPN22 also inhibits the signals induced by type I interferon (49), modulates macrophage polarization (50), and activates the inflammasome by dephosphorylating NLRP3 (51). A role of NLRP3 in Th cells was recently discovered (52).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the previously described phosphatases, PTPN22 promotes M(IL-4+IL-13) activation and reciprocally suppresses M(IFN␥+LPS) [78]. PTPN22 deficient macrophages treated with IL-4 and IL-13 have lower STAT6 phosphorylation and activation hence lower mRNA expression for arginase 1, Mrc1, and FIZZ1, and higher IL-10 production compared to M(IL-4+IL-13) from wild type mice [78].…”
Section: Ptpn22mentioning
confidence: 86%
“…PTPN22 deficient macrophages treated with IL-4 and IL-13 have lower STAT6 phosphorylation and activation hence lower mRNA expression for arginase 1, Mrc1, and FIZZ1, and higher IL-10 production compared to M(IL-4+IL-13) from wild type mice [78]. PTPN22 deficient macrophages treated with IFN␥ and LPS have higher NFB activation and higher production of IL-12p70, IL-23, and nitric oxide compared to M(IFN␥+LPS) from wild type mice [78]. Consistent with this, PTPN22 knockdown increases IFN␥-induced pro-inflammatory cytokine production in THP-1 cells, a human myelomonocytic cell line [82].…”
Section: Ptpn22mentioning
confidence: 96%
See 1 more Smart Citation
“…We have previously shown that PTPN22 is reduced in the intestine of IBD patients and that it plays a protective role during intestinal inflammation [24]. Further, PTPN22-deficient mice are more affected by DSS-induced colitis [25-27]. One possible explanation for reduced PTPN22 expression might be the fact that TNF-α and IL-1β suppress PTPN22 expression [28].…”
Section: Discussionmentioning
confidence: 99%